Communication Strategies Used in Bahasa Inggris Textbook for Grade Twelfth of Senior High School - Johan, Andrian Nuriza (Scripta : English Department Journal, 2019)
This article is based on a study which aims at the finding out components of commmunicaton stratedies and sufficiency of strategic competence in Bahasa Inggris textbook. The data analyzed are the models of speaking text taken from Bahasa Inggris textbook. There are 5 texts in the textbook. The finding of the study reveals there is no communication strategies used in the textbook.